Introducing 1, 3‐beta‐d‐glucan for screening and diagnosis of invasive fungal diseases in Australian high‐risk haematology patients: is there a clinical benefit?. Issue 3 (20th March 2022) - Garnham, Katherine; Halliday, Catriona L.; Rai, Neela J.; Jayawardena, Menuk; Hasan, Tasnim; Kok, Jen; Nayyar, Vineet; Gottlieb, David J.; Gilroy, Nicole M.; Chen, Sharon C.‐A.
Abstract: Background: Early, accurate diagnosis of invasive fungal disease (IFD) improves clinical outcomes. 1, 3‐beta‐d ‐glucan (BDG) (Fungitell, Associates of Cape Cod, Inc., Falmouth, MA, USA) detection can improve IFD diagnosis but has been unavailable in Australia. Aims: To assess performance of serum BDG for IFD diagnosis in a high‐risk Australian haematology population. Methods: We compared the diagnostic value of weekly screening of serum BDG with screening by Aspergillu s polymerase chain reaction and Aspergillus galactomannan in 57 at‐risk episodes for the diagnosis of IFD (proven, probable, possible IFD). Results: IFD episodes were: proven ( n = 4); probable ( n = 4); possible ( n = 18); and no IFD ( n = 31). Using two consecutive BDG results of ≥80 pg/mL to call a result 'positive', the sensitivity, specificity, positive predictive value and negative predictive value was 37.5%, 64.5%, 23.1% and 80.7% respectively. For invasive aspergillosis, test performance increased to 50%, 90.3%, 57.1% and 87.5% respectively if any two of serum BDG/ Aspergillus polymerase chain reaction/galactomannan yielded a 'positive' result. In proven/probable IFD, five of eight episodes returned a positive BDG result earlier (mean 6.6 days) than other diagnostic tests. False‐negative BDG results occurred in three of eight episodes of proven/probable IFD, and false positive in 10 of 31 patients with no IFD. Erratic patterns of BDG values predicted false positive results ( P = 0.03). Using serum BDG results, possible IFD were reassigned to either 'no' or 'probable' IFD in 44% cases. Empiric anti‐fungal therapy use may have been optimised by BDG monitoring in 38.5% of courses. Conclusions: The BDG assay can add diagnostic speed and value but was hampered by low sensitivity and positive predictive value in Australian haematology patients.